Validated Chromatographic Methods for Simultaneous Estimation of Cinnarizine in Binary Mixture with Domperidone and Paracetamol in Tablets - Mahrouse, Marianne A.; El-Zaher, Asmaa Ahmed; Al-Ghani, Ahmed Mohammed (Current Pharmaceutical Analysis, 2019)
Background: Cinnarizine, an antihistaminic drug, is commonly formulated in combination with domperidone and with paracetamol for treatment and prevention of motion sickness and migraine. Objective: The aim of this work was to develop new, simple, precise and selective chromatographic methods (RP-HPLC and TLC-densitometric methods) for the determination of these drugs. These methods can be used as analytical tools in the routine examination in quality control laboratories. Methods: The first method was RP-HPLC method, the separation was carried out on an Inertsil® ODS- 3V C18 column (250 mm 4.6 mm, 5 μm) using a mobile phase composed of methanol: acetonitrile (45: 55, v/v) at a flow rate of 1 ml/min. The detection was carried out at 220 nm. The second method was a TLC-densitometric method where the studied components were separated using a developing system composed of toluene: ethyl acetate: methanol: triethylamine (5: 4.3: 0.7: 0.5, v/v/v/v) on TLC silica gel 60 F254 plates, followed by densitometric scanning at 270 nm. Results: In RP-HPLC method, the peaks were sharp and well separated, the retention times were 5.25, 3.48 and 2.78 min, for cinnarizine, domperidone and paracetamol, respectively. Linearity was obtained over the concentration ranges 1-22, 0.75-16.5 and 25-550 μg/ml, for cinnarizine, domperidone and paracetamol, respectively. In TLC-densitometric method, good separation of spots and linear relationships were achieved over the concentration ranges of 0.2-2, 0.15-1.5 and 5-50 μg/spot, for cinnarizine, domperidone and paracetamol, respectively. Method validation was conducted according to ICH guidelines in terms of linearity, accuracy, selectivity, precision and robustness. Conclusion: The developed methods were applied for the determination of the cited drugs in tablets containing binary drug mixtures. The methods are simple and precise and can be used for routine analysis of the labelled drugs in combined dosage forms in quality control laboratories.
Keywords: TLC-densitometry